2001
DOI: 10.1002/jsfa.925
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal structure and function of broiler chickens on diets supplemented with a mannan oligosaccharide

Abstract: A study was conducted to evaluate the response of broiler chickens to a commercial synthetic mannan oligosaccharide, Bio-Mos 2 (BM), included in sorghum/lupin-based diets at 0.0, 1.0, 3.0 or 5.0 g kg À1 diet. The diets were fed between 7 and 28 days of age, and both the gross response and mechanisms involved were evaluated. The highest level of BM in the diet resulted in longer (P < 0.01) jejunal villi than those observed at other levels of supplementation. The RNA content of the ileal mucosal homogenate was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(141 citation statements)
references
References 28 publications
17
116
0
8
Order By: Relevance
“…Este efeito ocorreu provavelmente pelo efeito sinérgico entre o extrato de levedura e o prebiótico, pois, quando não se incluiu o extrato, este fato não foi observado. Por outro lado, Iji &Tivey (1998) e Iji et al (2001) observaram que o uso de oligossacarídeos pode ocasionar aumento no consumo de ração.…”
Section: Resultsunclassified
“…Este efeito ocorreu provavelmente pelo efeito sinérgico entre o extrato de levedura e o prebiótico, pois, quando não se incluiu o extrato, este fato não foi observado. Por outro lado, Iji &Tivey (1998) e Iji et al (2001) observaram que o uso de oligossacarídeos pode ocasionar aumento no consumo de ração.…”
Section: Resultsunclassified
“…However, the results showed that villus length was not affected by the plant extracts or prebiotic compounds. Dietary supplements such as prebiotic and bioactive compounds have been shown to have a trophic effect on the gut mucosal morphology in chickens (Iji et al 2001;Yamauchi et al 2006). It should be noted that these prior studies assessed compounds under hygienic husbandry practices and not in a disease-challenged condition as was the case of the present study.…”
Section: Gut Histomorphologymentioning
confidence: 87%
“…Commercially available mannanoligosaccharides are complex carbohydrates extracted from cell wall of yeast Saccharomyces cerevisiae. Added to feed, as entirely safe compounds, MOS appeared to be promising in suppressing enteric pathogens, modulating immune response, and improving integrity of the intestinal mucosa (Iji et al, 2001;Swanson et al, 2002;Elmusharaf et al, 2006). According to current knowledge, MOS prevent bacterial infection via mechanisms that are different from antibiotics, and therefore, circumvent the pathogens ability to develop resistance.…”
Section: Introductionmentioning
confidence: 99%